If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 6x = 48 Combine like terms: 10x + 6x = 16x 16x = 48 Solving 16x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '16'. x = 3 Simplifying x = 3
| 120(x/100)=1 | | 70(1-x)/100=1 | | 7(1-x)=1 | | 5/6x-3x=23 | | 7/2x-5/6x=1 | | 4s^2-11s=-7 | | 12y-50x=1500 | | 9=5x-69 | | -7y/6=12/-35 | | 6/7y=15/18 | | p^4r-rs=7p | | 0.3(x+5)0.5=8 | | 5c+23=8 | | Y=35x+3600 | | 8-(-16)+(-38)= | | 0.8-2(w-6)=30 | | 2x-13+24=7 | | 5-.5(8)+3=3m-8 | | x(2z-7)=16 | | P-22=19 | | 4x+9=4x-5 | | 5n-1-3n=2n+1 | | 0.7(x+14.1)=3(x+32.9) | | 8x=8+35 | | 0.7(x+14.1)=3(x+33.9) | | 8(2.92-2)+5(2.92)=22 | | 3/4n–18=1/4n–4 | | 6-(10*11)+10= | | 8(2.9-2)+5(2.9)=22 | | -1.00701051577(x^2-y^2-z^2+xy)=x^2+3y^2+3z^2-3xy-2xz-2yz | | 3/4(8) | | 1.00701051577(x^2-y^2-z^2+xy)=x^2+3y^2+3z^2-3xy-2xz-2yz |